TEORI QIRA’AH TARIKHIYAH DALAM MEMAHAMI AL-QUR’AN: (Studi Pemikiran Muhammad Talbi) - Hadari Hadari (Institut Agama Islam Sultan Muhammaad Syafiuddin Sambas, 2020)
Talbi is a North African-Islamic historian; a Muslim intellectual who questions the effectiveness of entrusting the fate of Islamic civilization entirely to traditional-orthodox interpretations. He is of the view that the new age also requires interpretation with a perspective that is open to renewal. With a historical approach sown with a humanist (humanist) perspective, he encourages a more open interpretation of the Koran through what he calls the al-qirā'ah approach. Talbi expressed his views on the Koran through (in broad outline) a historical approach and a human perspective. This approach he termed: al-qirā'ah al-maqāshidiyyah. From his various explanations, Talbi used historical principles and human values ​​as a guide in understanding the Koran. Talbi has been an observer of religious issues more often in his position as a historian who according to him is always armed with the spirit of humanity.